The Effect of Financial Performance, Corporate Governance, and Company Size on Corporate Social Responsibility Disclosure of Sustainability Report (E-Jurnal Akuntansi, 2026)
This study aims to determine the effect of profitability, leverage, CGPI, public ownership, and company size about CSR (Corporate Social Responsibility) disclosure in sustainability report. This study was performed on go public companies listed on CGPI (Corporate Governance Perception Index) 2014-2020 period. The sampling method used is the purposive sampling technique with total sample are 79 observations. Data analysis technique that used is multiple linear regression analysis. Based on analysis found that profitability, leverage, CGPI, and public ownership has positive effects on CSR disclosure of sustainability report. The companies that have high profitability, leverage, CGPI, public ownership tend to increase CSR disclosure of sustainability report. The result on company size variable has negative effect on CSR disclosure of sustainability report indicated that small companies tend to increase CSR disclosure of sustainability report.
Keywords: Financial Performance; Corporate Governance; Company Size; Sustainability Report